STUDI PERBANDINGAN KUALITAS PELAYANAN INDUSTRI PERBANKAN SYARIAH DENGAN KONVENSIONAL - RONI ANDESPA (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2016)
The study was conducted in West Sumatra with the object is shariah and conventional banking industry. Study the problems of shariah banking service quality comparison with a conventional one. This study aims to: (1) See if there are significant differences between the quality of service Islamic bank with conventional banks. (2) To see if there are significant differences between customer satisfaction Islamic bank with conventional banks. (3) To see if there are significant differences between customer loyalty Islamic banks with conventional banks. The research sample of 500 people. Data collection techniques used are Personally Administered Questionnaire. Using analysis of Independent Sample T-test. The study found no difference between the quality of services of conventional banks with shariah banks, but to the difference was not significant. The study also found no difference between conventional bank customer satisfaction with shariah banks, but to the difference was not significant. In addition the study also found no difference between conventional bank customers' loyalty to the shariah bank, but to the difference was not significant.